The Estimated Value of Losses and Insurance Due to Citarum River Flooding - Iin Irianingsih; Dwi Susanti; Alit Kartiwa; Forman Ivana S.S.S. (International Journal of Business, Economics, and Social Development, 2020)
Flooding in Citarum always happens in Bandung District which causes loss of property, household damage, diseases moreover decease. The government provides aid for flood victims, but the help is not cover losses. In this circumstance, people need insurance. This study aims to set up flood insurance based on economic conditions, areas, and losses due to flooding. To find out the conditions, interviewed the village chief of Baleendah. The analytical methods used are linear regression analysis and analysis method mix. Linear regression analysis was used to estimate flood losses that will serve as the sum insured in the form of insurance products. Analysis mixture consisting of identification areas, conditions, and alternative insurance models used to establish the right flood insurance for Baleendah. Results show the estimation of flood losses and flood insurance appropriate to the condition of Baleendah.